Size-resolved characterization of particles >10 nm emitted to air during metal recycling. (April 2023) - Lovén, Karin; Isaxon, Christina; Ahlberg, Erik; Bermeo, Marie; Messing, Maria E.; Kåredal, Monica; Hedmer, Maria; Rissler, Jenny
Highlights: For all processes, the vast number of particles emitted were nanoparticles (<100 nm). Chemical composition varied over particle size, specifically for the nanoparticles. Highest levels of airborne particles were found in the WEEE flow. The most abundant metals were Fe, Al, Zn, Pb and Cu. SEM/EDS analysis showed internally and externally mixed particles. Abstract: Background: In the strive towards a circular economy, metal waste recycling is a growing industry. During the recycling process, particulate matter containing toxic and allergenic metals will be emitted to the air causing unintentional exposure to humans and environment. Objective: In this study detailed characterization of particle emissions and workplace exposures were performed, covering the full size range from 10 nm to 10 µm, during recycling of three different material flows: Waste of electrical and electronic equipment (WEEE), metal scrap, and cables. Methods: Both direct-reading instruments (minute resolution), and time-integrated filter measurements for gravimetric and chemical analysis were used. Additionally, optical sensors were applied and evaluated for long-term online monitoring of air quality in industrial settings. Results: The highest concentrations, in all particle sizes, and with respect both to particle mass and number, were measured in the WEEE flow, followed by the metal scrap flow. The number fraction of nanoparticles was high for all material flows (0.66–0.86). The most abundant metals were Fe, Al, Zn, Pb and Cu. Other elements of toxicological interest were Mn, Ba and Co. Significance: The large fraction of nanoparticles, and the fact that their chemical composition deviate from that of the coarse particles, raises questions that needs to be further addressed including toxicological implications, both for humans and for the environment.